ATP triggers a robust intracellular [Ca2+]‐mediated signalling pathway in human synovial fibroblasts. Issue 8 (3rd July 2018) - Kondo, C.; Clark, R. B.; Kim, T. Y.; Belke, D.; Banderali, U.; Szerencsei, R. T.; Jalloul, A. H.; Schnetkamp, P. P. M.; Spitzer, K. W.; Giles, W. R.
Abstract : New Findings: What is the central question of this study? What are the main [Ca 2+ ]i signalling pathways activated by ATP in human synovial fibroblasts? What is the main finding and its importance? In human synovial fibroblasts ATP acts through a linked G‐protein (Gq ) and phospholipase C signalling mechanism to produce IP3, which then markedly enhances release of Ca 2+ from the endoplasmic reticulum. These results provide new information for the detection of early pathophysiology of arthritis. Abstract: In human articular joints, synovial fibroblasts (HSFs) have essential physiological functions that include synthesis and secretion of components of the extracellular matrix and essential articular joint lubricants, as well as release of paracrine substances such as ATP. Although the molecular and cellular processes that lead to a rheumatoid arthritis (RA) phenotype are not fully understood, HSF cells exhibit significant changes during this disease progression. The effects of ATP on HSFs were studied by monitoring changes in intracellular Ca 2+ ([Ca 2+ ]i ), and measuring electrophysiological properties. ATP application to HSF cell populations that had been enzymatically released from 2‐D cell culture revealed that ATP (10–100 μm ), or its analogues UTP or ADP, consistently produced a large transient increase in [Ca 2+ ]i . These changes (i) were initiated by activation of the P2 Y purinergic receptor family, (ii) required Gq ‐mediated signal transduction, (iii) did not involve a transmembrane Ca 2+ influx, but instead (iv) arose almost entirely from activation of endoplasmic reticulum (ER)‐localized inositol 1, 4, 5‐trisphosphate (IP3 ) receptors that triggered Ca 2+ release from the ER. Corresponding single cell electrophysiological studies revealed that these ATP effects (i) were insensitive to [Ca 2+ ]o removal, (ii) involved an IP3 ‐mediated intracellular Ca 2+ release process, and (iii) strongly turned on Ca 2+ ‐activated K + current(s) that significantly hyperpolarized these cells. Application of histamine produced very similar effects in these HSF cells. Since ATP is a known paracrine agonist and histamine is released early in the inflammatory response, these findings may contribute to identification of early steps/defects in the initiation and progression of RA. Abstract :